On the brink of education: Experiences of refugees beyond the age of compulsory education in Austria. (March 2018) - Atanasoska, Tatjana; Proyer, Michelle
This paper offers first-hand accounts of refugees beyond the age of compulsory education having arrived in Austria during the last five years. Their accounts were collected using qualitative interviews and a visual method to allow for different approaches towards their educational biographies. Nine individual and two group interviews (altogether with 16 young people) were conducted, where the majority of the young refugees are from Afghani background. All interviewees were older than 16 years. In addition, five expert interviews were conducted. Their experiences having arrived in a new country, the importance of education for them, and their aspirations in the new system became visible in the interviews. Arbitrary provision and the one-sided language focus of the system present challenges to the core of a (school) system that has proved resistant to the influx of pupils from many different cultural backgrounds for years. The results of this qualitative study show that educational segregation is common for this group, including having less chances to obtain a university entrance exam.